A case report on congenital rubella syndrome - Kanagadurga, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Congenital rubella syndrome (CRS) is a rare illness in infants that result from maternal infection with rubella virus during pregnancy. The case reported is a primigravida at 37.3 weeks of gestation with the complaints of headache, decreased urine output, bilateral pedal edema, puffiness of face and mild hydromnios suggesting pregnancy-induced hypertension (PIH). The previous data showed that the fetus had bone anomalies. Controversially the mother had rubella immune before 12 weeks of pregnancy but the report of nuchal translucency (NT) scan taken during 12 weeks of pregnancy was normal. On history mother denied any evidence of rubella infection during or recently before pregnancy which shows it was asymptomatic. She was treated for PIH. By lower segment caesarean section (LSCS), she delivered an alive boy baby who was acrocyanotic and had deformity in all long bones and enlarged liver. Placenta was found to be abnormal. The baby was under observation and the investigation confirmed CRS. Baby had bradycardia and was intubated on following days and found baby’s vocal cord shape was abnormal. Baby had seizures and could not tolerate weaning from ventilator. Before further investigations, the baby was discharged against medical advice. Though very rare, CRS was found to have many consequences to the fetus. Hence it is significant to rule out rubella infection for mother during or recently before pregnancy as a part of routine antenatal checkup as many of them are asymptomatic. All women should be insisted about getting vaccination for rubella minimum 28 days before planning for conception and should be abandoned for those who were already pregnant.